S n = n terms 2 ⋅ 4 1 + 2 ⋅ 4 ⋅ 6 1 ⋅ 3 + 2 ⋅ 4 ⋅ 6 ⋅ 8 1 ⋅ 3 ⋅ 5 + ⋯
For S n as defined above, S 1 0 = b a , where a and b are positive coprime integers. Find a + b + 2 7 1 7 1 6 .
Bonus: Find the closed form of S n then find S ∞ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S 1 0 = 2 . 4 1 + 2 . 4 . 6 1 . 3 + ⋯ + 2 . 4 . 6 . ⋯ . 2 2 1 . 3 . 6 . ⋯ . 2 1 S 1 0 = 2 . 4 4 − 3 + 2 . 4 . 6 . 1 . 3 ( 6 − 5 ) + 2 . 4 . 6 . 8 . 1 0 1 . 3 . 5 . ( 8 − 9 ) + ⋯ + 2 . 4 . 6 . ⋯ . 2 2 1 . 3 . 6 . ⋯ . 2 1 . ( 2 2 − 2 1 ) S 1 0 = 2 . 4 4 − 2 . 4 3 + 2 . 4 . 6 3 . 6 + 2 . 4 . 6 . 8 3 . 5 . 8 − 2 . 4 . 6 . 8 3 . 5 . 7 + ⋯ − 2 . 4 . 6 ⋯ 2 2 1 . 3 . 5 . ⋯ 2 1 ⟹ S 1 0 = 2 1 − ( 2 2 ) ! ! ( 2 1 ) ! ! = 2 1 − 4 . ( 1 1 ! ) 2 2 1 ! = 2 1 − 5 2 4 2 8 8 8 8 1 7 9 ∴ S 1 0 = 5 2 4 2 8 8 1 7 3 9 6 5 = b a ⟹ S ∞ = 2 1 Hence, the sum of a + b + 2 7 1 7 1 6 = 1 7 3 9 6 5 + 5 2 4 2 8 8 + 2 7 1 7 1 6 = 9 6 9 9 6 9 .
Problem Loading...
Note Loading...
Set Loading...
The n th term in the series is 2 2 n + 1 n ! ( n + 1 ) ! ( 2 n ) ! = 2 2 n 1 ( n 2 n ) − 2 2 n + 2 1 ( n + 1 2 n + 2 ) and hence the sum to N terms is S N = 2 1 − 2 2 N + 2 1 ( N + 1 2 N + 2 ) Thus S 1 0 = 2 1 − 2 2 2 1 ( 1 1 2 2 ) = 5 2 4 2 8 8 1 7 3 9 6 5 making the answer 1 7 3 9 6 5 + 5 2 4 2 8 8 + 2 7 1 7 1 6 = 9 6 9 9 6 9 .
Since 2 − 2 n ( n 2 n ) ∼ n π 1 as n → ∞ , using Stirling's approximation, we deduce that lim N → ∞ S N = 2 1 .